2019
DOI: 10.1177/0886260519888207
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Classroom Normative Climate and the Perpetration of Teen Dating Violence Among Secondary School Students

Abstract: The aim of this study was to investigate how classroom normative climate regarding the perpetration of teen dating violence (TDV) was related to adolescents’ self-reported perpetration of (verbal/emotional, threatening, relational, physical, and sexual) violence within romantic relationships in the previous 12 months. Based on Theory of Normative Conduct, we hypothesized that higher classroom levels of TDV perpetration were associated with a higher likelihood of individual TDV perpetration. Data were drawn fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 67 publications
5
22
0
Order By: Relevance
“…The highest perpetration rate of psychological violence for male adolescents was identified in Spain (95.3%, Fernández‐Fuertes & Fuertes, 2010), and the lowest in Denmark (19.9%, Karsberg et al., 2018). Only one gender difference was reported as significant, showing that German female adolescents reported higher rates of psychological violence perpetration than German male adolescents (59.0% vs. 42.7%, Beckmann et al., 2019).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The highest perpetration rate of psychological violence for male adolescents was identified in Spain (95.3%, Fernández‐Fuertes & Fuertes, 2010), and the lowest in Denmark (19.9%, Karsberg et al., 2018). Only one gender difference was reported as significant, showing that German female adolescents reported higher rates of psychological violence perpetration than German male adolescents (59.0% vs. 42.7%, Beckmann et al., 2019).…”
Section: Resultsmentioning
confidence: 96%
“…However, considering studies in other countries that are also based on the CADRI revealed that one study from Belgium (Glowacz et al., 2018) and one from Germany (Kliem et al., 2018) were similar to each other in terms of sexual TDV victimization and perpetration but different from all other mentioned Spanish studies. However, in terms of physical TDV perpetration, some similarity was found between a German study (Beckmann et al., 2019) and two Spanish studies (Calvete et al., 2016; Izaguirre & Calvete, 2017), leaving the picture of comparison between the countries inconclusive.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Sport, in addition to school and family, is an important context in which children’s and adolescents’ experiences can be greatly influenced by the adults who take care of them (e.g., parents, teachers, and coaches) and by other children/adolescents (e.g., peers). Recent studies conducted in the family and school contexts have also demonstrated the relevance of conducting research with children and adolescents to measure parental neglect ( Vanderminden et al, 2019 ), corporal punishment ( Finkelhor et al, 2019 ) as well as teen dating violence ( Beckmann et al, 2019 ). Also, as stated by Vertommen and Parent (2020) , “including children’s voices and experiences in IV in sport research would be a welcome and valuable innovation” (p. 389).…”
Section: Introductionmentioning
confidence: 99%
“…School, or even a classroom as a narrower area, is perceived as an important factor for the socialization of dating violence in adolescents [32]. As for the research, it is related particularly to a relative aspect of school climate and social support.…”
Section: Introductionmentioning
confidence: 99%